A review of the use of direct seeding and seedling plantings in restoration: what do we know and where should we go?. Issue 4 (13th June 2015) - Palma, Ana Cristina; Laurance, Susan G.W.; Marrs, Rob
Abstract Questions To select the best method to restore an ecosystem requires an understanding of the various outcomes commonly achieved through different restoration techniques. What method results in the most timely and cost‐effective means of reinstating biodiversity and restoring ecosystem functions and services? Methods We explored the efficacy and costs of two re‐vegetation techniques commonly used in ecosystem restoration: direct seeding and planting of seedlings. Our analysis focused on 120 scientific peer‐reviewed publications reporting on experiments using seeds or seedlings, and encompassed a range of ecosystems such as wetlands, savannas and forests. We examined current restoration issues, including species diversity, survival, species selection, costs and how future climate change may influence restoration efforts. Results Direct seeding experiments used more species than seedling studies, yet showed lower survivorship. Species availability is the major constraint in the selection of which species were used, regardless of the approach employed. Although costs are extremely important when planning a restoration project, few published findings report on the economic aspects of ecosystem restoration. Further, we did not find any study addressing the impacts of global climate change on restoration programmes or how studies should consider future shifts in the environment. Conclusions Our results highlight the need for restoration experiments to explore more species. Restoration efforts are in need of detailed reporting that includes time frames and costs. We need to consider future climate scenarios that will affect ecosystem restoration efforts.